Analyzing the relationship between organizational resources and organizational performance moderated by organizational culture in the Malaysian electrical and electronics industry - Zulrina Efriza, Zardi (2022)
Economists concur that the three elements driving the country’s economic development are the employment rate, productivity, and inflation rate. Since the manufacturing sector makes notable contributions toward a country’s economic development, it has been the focus of many researchers. In recent decades, the manufacturing sector has experienced rapid evolution. Start from mass production using an intensive labour force in production lines to using robotics to increase efficiency, the manufacturing industry is constantly expanding with new automation elements. Today, the next phase of evolution, known as the Fourth Industrial Revolution or Industry 4.0, has witnessed an improvement in the manufacturing industry toward producing technologically complex products. However, specific cultures may not hold relevance in the current business environment. Thus, this research aimed to examine the relationship between organizational resources with organizational performance, including the organizational culture functioning as the moderator of the link between organizational resources and performance. The survey method was applied in this study, where data were tested using 287 Electrical and Electronics Industry respondents listed in the Federation of Malaysian Manufacturers and Malaysia External Trade Development Corporation. Using Partial Least Square (PLS) as a tool to analyse the relationship, it was found that a positive and significant relationship was present between organizational resources (entrepreneurial orientation, innovation capability, intellectual capital, and technology orientation) and organizational performance. The role of organizational culture as a moderating variable was then established, leading to the finding of the importance of organizational culture on the relationship between organizational resources (innovation capability, entrepreneurial orientation, intellectual capital, and technology orientation) and organizational performance. The study has implications for E&E organizations, academicians and researchers. This study is also expected to increase organizational performance by creating a benchmark for all Malaysian E&E organizations to improve their innovation, knowledge, technology and competence.